Androgen receptor variant shows heterogeneous expression in prostate cancer according to differentiation stage - Ada Gjyrezi (Nature Portfolio, 2021)
Ada Gjyrezi et al. show that ddPCR can be used to accurately measure androgen receptor variant (AR-V) expression levels in single circulating tumor cells (CTCs) from prostate cancer patients. They show that current methods for isolating CTCs tend to underestimate the prevalence of AR-V and that a specific variant, AR-v567es, could be potentially used as a biomarker for an aggressive subtype of prostate cancer.